Deficits in learning are greater than memory dysfunction in preclinical Alzheimer's disease: Neuropsychology: Neuropsychological correlates of pathology — Novel and standard cognitive markers of disease. (7th December 2020) - Lim, Yen Ying; Baker, Jenalle E.; Bruns, Loren; Mills, Andrea; Fowler, Christopher J.; Fripp, Jurgen; Rainey‐Smith, Stephanie R.; Ames, David; Masters, Colin L.; Maruff, Paul T.
Abstract: Background: Reports from longer studies of preclinical Alzheimer's disease (i.e., Aβ+ cognitively normal older adults) now show that performance on memory tests remains stable across re‐assessments, whereas in matched Aβ‐ controls, performance improves substantially (i.e. a practice effect). Such observations have led to proposals that the absence of expected practice effects may provide a superior cognitive marker of Aβ+ in older adults. However, an alternative explanation may be that disruption to MTL areas in preclinical AD manifest more strongly as deficits in learning than as a progressive decline in memory recall. Using a test designed specifically to measure learning over days, we aimed to determine the extent to which deficits in learning over 6 days are associated with Aβ+ and hippocampal volume in CN adults. Method: Eighty CN older adults who had undergone positron emission tomography (PET) neuroimaging to determine Aβ status (n=42 Aβ‐ and 38 Aβ+), magnetic resonance imaging (MRI) to determine hippocampal and ventricular volume and repeated assessment of memory were recruited from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study. Participants completed the Online Repeatable Cognitive Assessment‐Language Learning Test (ORCA‐LLT), which required they learn associations between 50 Chinese characters and their English language equivalents over 6 days. ORCA‐LLT assessments were supervised on the first day, and were completed remotely online for all remaining days. Result: Learning curves in the Aβ+ CNs were significantly worse than those in matched Aβ‐ CNs, with the magnitude of this difference very large (d=2.16, p <.001) (Figure 1), and greater than differences between these groups for memory decline since their enrolment in AIBL (d=0.52, p =.021), or memory impairment at their most recent visit. In Aβ+ CN adults, slower rates of learning were associated with smaller hippocampal, and larger ventricular volumes. Conclusion: These results suggest that in CNs, Aβ+ is associated more strongly with a deficit in learning than any aspect of memory dysfunction. Slower rates of learning in Aβ+ CNs were associated with hippocampal volume loss. Considered together, these data suggest that the primary cognitive consequence of Aβ+ is a failure to benefit from experience when exposed to novel stimuli, even over very short periods.